Impact of HIV treat-all and complementary policies on ART linkage in 13 PEPFAR-supported African countries - Anna Russell; Andre R. Verani; Sherri Pals; Valamar M. Reagon; Lorraine N. Alexander; Eboni T. Galloway; Mayer Magdalene Mange; Pearl Kalimugogo; Ponesai Nyika; Yasmine Moussa Fadil; Appolonia Aoko; Fred Mugyenyi Asiimwe; et al. (BMC, 2023)
Abstract Background In 2015, the World Health Organization recommended that all people living with HIV begin antiretroviral treatment (ART) regardless of immune status, a policy known as 'Treat-All to end AIDS', commonly referred to as Treat-All. Almost all low- and middle-income countries adopted this policy by 2019. This study describes how linkage to treatment of newly diagnosed persons changed between 2015 and 2018 and how complementary policies may have similarly increased linkage for 13 African countries. These countries adopted and implemented Treat-All policies between 2015 and 2018 and were supported by the U.S. Government's President's Emergency Plan for AIDS Relief (PEPFAR). The focuses of this research were to understand 1) linkage rates to ART initiation before and after the adoption of Treat-All in each country; 2) how Treat-All implementation differed across these countries; and 3) whether complementary policies (including same-day treatment initiation, task-shifting, reduced ART visits, and reduced ART pickups) implemented around the same time may have increased ART linkage. Methods HIV testing and treatment data were collected by PEPFAR country programs in 13 African countries from 2015 to 2018. These countries were chosen based on the completeness of policy data and availability of program data during the study period. Program data were used to calculate proxy linkage rates. These rates were compared relative to the Treat All adoption period and the adoption of complementary policies. Results The 13 countries experienced an average increase in ART linkage of 29.3% over the entire study period. In examining individual countries, all but two showed increases in linkage to treatment immediately after Treat All adoption. Across all countries, those that had adopted four or more complementary policies showed an average increased linkage of 39.8% compared to 13.9% in countries with fewer than four complementary policies. Conclusions Eleven of 13 country programs examined in this study demonstrated an increase in ART linkage after Treat-All policy adoption. Increases in linkage were associated with complementary policies. When exploring new public health policies, policymakers may consider which complementary policies might also help achieve the desired outcome of the public health policy.